Pengaruh Promosi, Ulasan Produk, Dan Metode Pembayaran Terhadap Keputusan Pembelian Pada Marketplace Shopee Food (Studi Kasus Pada Pengguna Aplikasi Shopee Food Di Kota Malang) - Masruhan, Helmy Naufal; Wahono, Budi; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Shopee Food is an application that provides food delivery services with a wide selection of food and drinks online using only a smartphone. The purpose of this study was to determine whether promotions, product reviews, and payment methods influence purchasing decisions on the Shopee Food application. This type of research is explanatory research using quantitative methods. The population in this study were users of the Shopee Food application in Malang City. The number of samples used was 96 respondents who were determined using the Lameshow formula. The results showed that promotion has a positive effect and has a significant effect on purchasing decisions, product reviews have a positive effect and have a significant effect on purchasing decisions. And the Payment Method has a negative effect and has a significant effect on Purchasing Decisions. Keywords: Promotion, Product Review, Payment Method, Purchase Decision